1999
DOI: 10.1159/000016549
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Oolong Tea Extract on Caries–Inducing Properties of Mutans Streptococci

Abstract: The inhibitory effects of oolong tea extract (OTE) on the caries–inducing properties of mutans streptococci were examined in vitro. OTE reduced the rate of acid production by mutans streptococci accompanied with the retardation of growth rate of mutans streptococci, while the action by chromatographically isolated oolong tea polyphenol (OTF6) was weak. On the other hand, both oolong tea products decreased cell surface hydrophobicity of almost all the oral streptococci examined in the present study, and also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 5 publications
8
120
0
3
Order By: Relevance
“…The sucrose-independent adherence of strain C1 to salivacoated hydroxyapatites (SHA) was examined by the method of Matsumoto et al (10) and found to be significantly lower than that of strain MT8148 (PϽ0.0001), while A1 showed a similar level of adherence to that of MT8148. Although the dextran-binding activity of strain A1, examined by the method of Lis et al (8), was lower than that of strain MT8148, the difference was not significant.…”
Section: The Role Of Glucan-binding Proteins In the Cariogenicity Of mentioning
confidence: 99%
“…The sucrose-independent adherence of strain C1 to salivacoated hydroxyapatites (SHA) was examined by the method of Matsumoto et al (10) and found to be significantly lower than that of strain MT8148 (PϽ0.0001), while A1 showed a similar level of adherence to that of MT8148. Although the dextran-binding activity of strain A1, examined by the method of Lis et al (8), was lower than that of strain MT8148, the difference was not significant.…”
Section: The Role Of Glucan-binding Proteins In the Cariogenicity Of mentioning
confidence: 99%
“…As known that adhesion is important to colonization of microorganisms pathologic. Adhesion of S. mutans to the surface of the tooth is the stage important in the formation of biofilm and led to the development of caries [11,12,13].…”
Section: IImentioning
confidence: 99%
“…Cell surface hydrophobicity of S. mutans related to surface protein of S. mutans. Polyphenol polymers from plant material can react with surface proteins of S. mutans, causing changes the cell surface hydrophobicity of S. mutans, decline in cellular aggregation and the number of S. mutans attached to hydroxyapatite [11]. The content of eugenyl acetate and polyphenol, namely quercetin, mirisetin, taxifolin, and tannin in Jamblang leaves extract, may play a role in decreasing the number of S. mutans attached to HA [13,15,18].…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura consultada não relata nada sobre a síntese de polissacarídeos com os três chás estudados. Porém quando analisados trabalhos com chá preto, este se mostra inibidor da síntese e conseqüentemente do poder de aderência da placa dentária 17,24,32,35,36,60 .…”
Section: D D Di I Is S Sc C Cu U Us S Ss S Sã ã ãO O O D D Di I Is unclassified